Local recycled water in Sydney: A policy and regulatory tug-of-war. (1st April 2017) - Watson, Rachel; Mukheibir, Pierre; Mitchell, Cynthia
Abstract: Local recycled water (LRW) can potentially contribute to resilient and sustainable urban water services critical to liveable cities. Investment in these systems has increased rapidly in Australia in the past 10 years, yet public and private investment in these systems can still be difficult, complex, costly and risky. An in depth case study analysis of Sydney, revealed that while the local policy, institutional and regulatory environment is on the surface conducive to the uptake of local recycled water, actual practice has surprisingly mitigated against further and broader investment in these systems. These instruments are often counteracted by multiple opposing levers that in some instances were developed for entirely different purposes. The generalizable insight is that a systematic, systemic, detailed review of these instruments and levers can reveal unexpected contradictions and provide a strong and defensible base from which to develop strategies to address unintended consequences and remove barriers to future investment. Graphical abstract: The policy and regulatory tug-of-war for local recycled water. Highlights: Recycled water in Sydney has increased rapidly in the last decade. Investment has been supported by numerous policy and regulatory incentives. Policy lever benefits can be undermined by unintentionally-opposing levers. Exploring the oppositional nature of these levers helps explain existing investment limits. Identifying critical interplay between levers helps address unintended consequences.